FILSAFAT ILMU KARL R. POPPER DAN THOMAS S. KUHN SERTA IMPLIKASINYA DALAM PENGAJARAN ILMU - Subekti, Slamet (HUMANIKA, 2015)
This article discusses about philosophy of science according to Karl R. Popper and Thomas S. Kuhn. There are similarities and differences between their views about how progress and what function of science.Apparently both Popper and Kuhn agree that science does not proceed by induction. However Kuhn disagrees with the view that science progresses by falsifiability through conjectures and refutations, but occurance by paradigm shift. Popper and Kuhn’s disagreement amounted to a distinction between two functions within the practice of science, one of criticism (Popper) and one of puzzle solving (Kuhn).Science education implies the teaching and learning of science interesting and fruitful in one hand, and teachers should be role models to students in the other hand